Derrida on Being as Presence - White, David A. (Walter de Gruyter, Inc., 2017)
Jacques Derrida's extensive early writings devoted considerable attention to "being as presence," the reality underlying the history of metaphysics. In Derrida on Being as Presence: Questions and Quests, David A. White develops the intricate conceptual structure of this notion by close exegetical readings drawn from these writings. White discusses cardinal concepts in Derrida's revamping of theoretical considerations pertaining to language-signification, context, negation, iterability-as these considerations depend on the structure of being as presence and also as they ground "deconstructive" reading. White's appraisal raises questions invoking a range of problems. He deploys these questions in conjunction with thematically related quests that arise given Derrida's conviction that the history of metaphysics, as variations on being as presence, has concealed and skewed vital elements of reality. White inflects this critical apparatus concerning being as presence with texts drawn from that history-e.g., by Plato, Aristotle, Bacon, Hume, Kant, Whitehead. The essay concludes with a speculative ensemble of provisional categories, or zones of specificity. Implementing these categories will ground the possibility that philosophy in general and metaphysics in particular can be pursued in ways which acknowledge the relevance of Derrida's thought when integrated with the philosophical enterprise as traditionally understood.